A DNA Encoding Image Encryption Algorithm Based on Chaos - Li Huang; Cong Ding; Zhenjie Bao; Haitao Chen; Changsheng Wan (Mathematics)
With the development of society and the Internet, images have become an important medium for information exchange. To improve the security of image encryption and transmission, a new image encryption algorithm based on bit-plane decomposition, DNA encoding and the 5D Hamiltonian conservative chaotic system is proposed. This encryption scheme is different from the traditional scrambling and diffusion methods at the level of image spatial pixels but encodes images into DNA strands and completely scrambles and diffuses operations on the DNA strands to ensure the security of images and improve the efficiency of image encryption. Firstly, the initial value sequence and convolution kernel of the five-dimensional Hamiltonian conservative chaotic system are obtained using SHA-256. Secondly, the bit-plane decomposition is used to decompose the image into high-bit and low-bit-planes, combine with DNA encoding to generate DNA strands, hide the large amount of valid information contained in the high-bit-planes, and preliminarily complete the hiding of the image information. In order to further ensure the effect of image encryption, seven DNA operation index tables controlling the diffusion process of the DNA strands are constructed based on the DNA operation rules. Finally, the scrambled and diffused DNA strand is decomposed into multiple bit-planes to reconstruct an encrypted image. The experimental results and security analysis show that this algorithm has a large enough key space, strong key sensitivity, high image encryption quality, strong robustness and high encryption efficiency. In addition, it can resist statistical attacks, differential attacks, and common attacks such as cropping attack, noise attack and classical attack.